PENINGKATAN KESADARAN HUKUM TENTANG KEKERASAN SEKSUAL PADA PEREMPUAN DAN ANAK DI KELURAHAN LATERI KOTA AMBON - Judy Marria Saimima; Elvira Liminanto; Zacilasi Wasia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
Sexual violence that occurs to a woman and child is due to a value system that places women and children as weak and inferior beings compared to men. It is necessary to have a good legal understanding of the community regarding sexual violence so that they are able to act when experiencing sexual violence. This activity is carried out by identifying the problems that exist in the area, then the community is given an understanding in order to increase legal awareness about sexual violence against women and children. An act that can be categorized as sexual violence is when the act is carried out without consent or is not desired. The PKDRT Law, the Child Protection Law, the Criminal Code and even the Pornography Law have indeed regulated protection for victims of sexual violence against children and women, but that is not enough to protect victims, because sexual violence protection is not limited to theories and regulations but is more broadly applicable to awareness of society as a social being itself.